High Flow Nasal Cannula Oxygen Therapy in Children; a Review - Cristina García-Muro; Cristina Toledo-Gotor; Verónica Jiménez-Escobar; Isabel Sáenz-Moreno; Eduardo Esteban-Zubero (AlQalam Journal of Medical and Applied Sciences, 2020)
High flow nasal cannula (HFNC) oxygen therapy is a non-invasive respiratory support consisting in the administration of heated, humidified and blended air/oxygen delivered via nasal cannula. The inspired oxygen concentration can be varied from 21% to 100%, therefore giving a greater ability to titrate the concentration of oxygen delivered. Its potential benefits include; increase fraction of oxygen and carbon dioxide in the alveoli, a decrease in damage to upper airway mucosa, reduction of upper-airway resistance, reduction of the metabolic cost of gas conditions, and ventilation improvement by providing a continuous positive airway pressure. However, this technique has contraindications, including severe hypoxia, hemodynamic instability, pneumothorax, upper airway abnormalities and facial bone or skull base trauma. In addition, it should not be used in patients with hypercapnia. There has been an increase in the use of HFNC in pediatrics in recent years, despite the fact that there is little evidence of its effectiveness and safety in children Its main indication is acute bronchiolitis. Nevertheless, other respiratory diseases including asthma, pneumonia and post-extubation respiratory support have been studied. The aim of this article is to review the available evidence on the use of HFNC in most frequent respiratory diseases in pediatric age, including bronchiolitis, asthma and pneumonia.